(untitled) (Analysis in Theory and Applications, 2025)
We prove the boundedness of multilinear Bochner-Riesz operator on central Morrey spaces with variable exponents. Moreover, we also show that the variable exponent Lipschitz commutator of Bochner-Riesz operator are bounded on above spaces. As applications, we also obtain the bounds of the commutators generated by λ-central BMO functions and Bochner-Riesz operators on central Morrey spaces with variable exponents.